An innovative approach combining metabarcoding and ecological interaction networks for selecting candidate biological control agents. Issue 12 (21st September 2021) - Ollivier, Mélodie; Lesieur, Vincent; Tavoillot, Johannes; Bénetière, Fanny; Tixier, Marie‐Stéphane; Martin, Jean‐François
Abstract: Classical biological control (CBC) can be used to decrease the density of invasive species to below an acceptable ecological and economic threshold. Natural enemies specific to the invasive species are selected from its native range and released into the invaded range. This approach has drawbacks, despite the performance of specificity tests to ensure its safety, because the fundamental host range defined under controlled conditions does not represent the actual host range in natura, and these tests omit indirect interactions within community. We focus on Sonchus oleraceus (Asteraceae), a weed species originating from Western Palearctic that is invasive in many countries and notably in Australia. We explore how analyses of interaction network within its native range can be used to (a) inventory herbivores associated to the target plant, (b) characterize their ecological host ranges and (c) guide the selection of candidate biocontrol agents considering interactions with species from higher trophic levels. Arthropods were collected from plant community sympatric to S. oleraceus, in three bioclimatic regions, and interactions were inferred by a combination of molecular and morphological approaches. The networks reconstructed were structured in several trophic levels from basal species (plant community), to intermediate and top species (herbivorous arthropods and their natural enemies). The sub‐network centred on S. oleraceus ‐related interactions contained 116 taxa and 213 interactions. We identified 47 herbivores feeding on S. oleraceus, 15 of which were specific to the target species. Some discrepancies with respect to published findings or conventional specificity tests suggested possible insufficient sampling effort for the recording of interactions or the existence of cryptic species. Among potential candidate agents, six exhibited interactions with natural enemies. Synthesis and applications . Adopting a network approach as prerequisite step of the classical biological control programme can provide a rapid screening of potential agents to be tested in priority. Once ecological host range defined, we suggest that priority should be given to agent used by a minimum species, and, when they exist, to agents that possess enemies from the most distant taxonomical group from those occurring in the range of introduction. Abstract : Adopting a network approach as prerequisite step of the classical biological control programme can provide a rapid screening of potential agents to be tested in priority. Once ecological host range defined, we suggest that priority should be given to agent used by a minimum species, and, when they exist, to agents that possess enemies from the most distant taxonomical group from those occurring in the range of introduction. Résumé: La lutte biologique classique peut être utilisée pour réduire la densité des espèces envahissantes sous un seuil écologiquement et économiquement acceptable. Des ennemis naturels spécifiques de l'espèce envahissante sont alors sélectionnés dans son aire d'origine et relâchés dans l'aire envahie. Cette approche présente des inconvénients malgré la réalisation de tests de spécificité pour garantir son innocuité. En effet, la gamme d'hôtes fondamentale définie dans des conditions contrôlées ne représente pas la gamme d'hôtes réelle réalisée in natura, et ces tests omettent les interactions indirectes au sein de la communauté. Cette étude se concentre sur Sonchus oleraceus (Asteraceae), une adventice originaire du Paléarctique occidental qui est envahissante dans de nombreux pays et notamment en Australie. Nous explorons comment l'analyse du réseau d'interactions dans son aire d'origine peut permettre de (a) inventorier les herbivores associés à la plante cible, (b) caractériser leurs gammes d'hôtes écologiques, et (c) guider la sélection d'agents de biocontrôle candidats en tenant compte des interactions avec les espèces de niveaux trophiques supérieurs. Des arthropodes ont été collectés dans des communautés végétales sympatriques de S. oleraceus, dans trois régions bioclimatiques, et les interactions ont été déduites par une combinaison d'approches moléculaires et morphologiques. Les réseaux reconstruits étaient structurés en plusieurs niveaux trophiques, des espèces basales (communauté végétale) aux espèces intermédiaires et supérieures (arthropodes herbivores et leurs ennemis naturels). Le sous‐réseau centré sur les interactions liées à S. oleraceus contenait 116 taxons et 213 interactions. Nous avons identifié 47 herbivores se nourrissant de S. oleraceus, dont 15 étaient spécifiques de l'espèce cible. Certaines divergences par rapport à la littérature ou aux tests de spécificité conventionnels suggèrent un effort d'échantillonnage insuffisant pour la détection des interactions ou l'existence d'espèces cryptiques. Parmi les agents candidats potentiels, 6 présentaient des interactions avec des ennemis naturels. Synthèse et applications . L'adoption d'une approche par reconstruction des réseaux écologiques comme étape préalable du programme de lutte biologique classique peut fournir une sélection rapide d'agents potentiels à tester en priorité. Une fois la gamme d'hôtes écologiques définie, nous suggérons que la priorité soit donnée aux agents utilisés par un minimum d'espèces et, lorsqu'ils existent, à des agents qui possèdent des ennemis naturels taxonomiquement distants de ceux présents dans l'aire d'introduction.